Stem Cell-Friendly Scaffold Biomaterials: Applications for Bone Tissue Engineering and Regenerative Medicine - Zhang, Yongtao; Wu, Di; Zhao, Xia; Pakvasa, Mikhail; Tucker, Andrew Blake; Luo, Huaxiu; Qin, Kevin H.; Hu, Daniel A.; Wang, Eric J.; Li, Alexander J.; Zhang, Meng; Mao, Yukun; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
Bone is a dynamic organ with high regenerative potential and provides essential biological functions in the body, such as providing body mobility and protection of internal organs, regulating hematopoietic cell homeostasis, and serving as important mineral reservoir. Bone defects, which can be caused by trauma, cancer and bone disorders, pose formidable public health burdens. Even though autologous bone grafts, allografts, or xenografts have been used clinically, repairing large bone defects remains as a significant clinical challenge. Bone tissue engineering (BTE) emerged as a promising solution to overcome the limitations of autografts and allografts. Ideal bone tissue engineering is to induce bone regeneration through the synergistic integration of biomaterial scaffolds, bone progenitor cells, and bone-forming factors. Successful stem cell-based BTE requires a combination of abundant mesenchymal progenitors with osteogenic potential, suitable biofactors to drive osteogenic differentiation, and cell-friendly scaffold biomaterials. Thus, the crux of BTE lies within the use of cell-friendly biomaterials as scaffolds to overcome extensive bone defects. In this review, we focus on the biocompatibility and cell-friendly features of commonly used scaffold materials, including inorganic compound-based ceramics, natural polymers, synthetic polymers, decellularized extracellular matrix, and in many cases, composite scaffolds using the above existing biomaterials. It is conceivable that combinations of bioactive materials, progenitor cells, growth factors, functionalization techniques, and biomimetic scaffold designs, along with 3D bioprinting technology, will unleash a new era of complex BTE scaffolds tailored to patient-specific applications.